The Similarities between the Story of Joseph and Moses (peace be upon Them): An Objective Study - Ismail, Manhal Yahya (Journal of Tikrit University for Humanities, 2020)
Allah Almighty told the stories of the prophets with their nations to enable human beings to reflect upon them and to take caution against falling into the mistakes of those nations against their prophets. The present study sheds the light upon the similarities between the stories of Joseph and Moses (peace be upon them). Despite the long time between the two prophets, there are remarkable similarities in most of the events of the two stories.